Crime of Plagiarism - الحيدري, جمال ابراهيم; علي, علياء يونس (Journal of Legal Sciences, 2019)
The information and knowledge are the main source of wealth in modern age. They have become the source of power for the state and the base for its advancement and prosperity and a proof if the scientific and technological progress of the age. This knowledge can only reach an advance stage through the scientific research by scholars and researchers. Knowledge is based on an accumulate basis that depends on the scientific product of the scholars and research books for the purpose of developing them. That poses on the scholar scientific fidelity when conveying this information from the scholarly writings as the creator of this information is the holder of the copyright. Otherwise the research bears the liability of copyright infringement by committing the crime of Plagiarism of efforts of others. Consequently, he bears the criminal liability accursed from that.  This will be discussed in three inquiries: the first one is concerned with the definition of Plagiarism; the second inquiry is devoted to the elements of the crime while the third is concerned with the acrrued accrued